Borrowing Words In The Translation Of English Into Indonesian Found In Emirates Airline Website - Dewantara, Dewa Ayu Radina Putri; Qomariana, Yana; Ayu Made Puspani, Ida (Peneliti.net, 2026)
Translation reproduces a language in the receiving language according to the closest natural equivalent to the source language. The borrowing procedure in translation directly transfers the source language to the target language. The study aims to identify and analyze the types of borrowing words and find the type of borrowing word mostly found on the Emirates Airline Website, translated from English to Indonesian. Data was collected using documentation, note-taking, and mixed methods, namely qualitative and quantitative, to analyze it. The data was analyzed using the theory proposed by Molina and Albir (2002). The analysis results show that both borrowing procedures are found on the Emirates Airline website, which is translated from English to Indonesian. The total data of the two types of borrowing words found is 440, with details of 111 being pure borrowing types, and 329 being naturalized borrowing types, so the borrowing most commonly found in the object of research is naturalized. In pure borrowing, the word is translated directly without modification or change, and naturalized borrowing is the process of adopting a word or expression from the source language and modifying it to fit the standards of the target language, particularly the spelling conventions. The adjustments that occur include various spelling changes, such as switching from consonants to vowels and vice versa, changes between consonants and other consonants, or vowels with other vowels. In addition, there are also omissions of vowels or consonants in words when translated into the target language, the addition of new vowels or consonants, and changes in endings with vowels.